the first experience of phakoemulsification with vacuum trabeculoplasty ab interno for combined cataract and glaucoma - V. N. Trubilin; N. A. Kaira; A. V. Trubilin (Oftalʹmologiâ)
Purpose: to describe of a new effective method of combined treatment of patients with primary open- angle glaucoma with mod- erately elevated intraocular pressure and cataract.Methods: Studies have been conducted among 30 patients (30 eyes) from 46 to 85 years with a combination of cataract of varying degrees of maturity and open-angle glaucoma of different stages. In addition to the standard techniques there were used special clini- cal and functional methods of research: optical cogerent tomography of the anterior segment of the eye Visante OCt (Carl Zeiss, Ger- many), glaucomatous cupping and thickness of nerve fibers study using confocal scanning laser ophthalmoscope HRt II (Heidelberg Engineering, Germany). In accordance with the target patients were divided into 2 groups: the basic group consisted of 15 patients (15 eyes) aged 63 to 76 years with primary open angle glaucoma of 1-2 stages and cataracts of varying degrees of maturity. In both groups there was performed the ultrasonic phakoemulsification of the lens on the phakoemulsificator Infinity (Alcon, US).Results: the analysis of intraocular pressure measurements showed that among patients from I and II group eye pressure had a downward trend in the early postoperative period, however, the average dynamics of reduction of the intraocular pressure in the group of patients where phakoemulsification and vacuum trabeculoplasty ab interno performed was higher than in the control group. In the gonioscopy of the corner of the anterior chamber the clinical presentation remained stable throughout the period of observation. In the postoperative period among patients in the main observation group according to OCt it was noted changing the depth of the anterior chamber of eye towards its increase by an average of 1.39 mm, as well as increasing the angle of the anterior chamber at an average of 9.98.Conclusion: Phakoemulsification with IOL implantation combined with vacuum trabeculoplasty ab interno is not more, but even less traumatic than the methods of surgical treatment of cataract and glaucoma. It has been established and proven that the depth of anterior chamber of eye changes towards its increase, as well as the distension of the angle of the anterior chamber among all the patients who had surgery of cataract phakoemulsification combined with the vacuum trabeculoplasty ab interno.